Improvement of a recombinant β-glucosidase activity of a sequence derived from metagenome database of Binh Chau hotspring - Thuy, Tran Thanh; Nhung, Lai Thi Hong; Xuan, Le Thi Thanh; Thoa, Nguyen Kim (Vietnam Journal of Biotechnology, 2020)
Metabolic products obtaining from microorganisms of geothermal ecologies often show special characteristics which help their cells to survive, grow and develop under extreme conditions. Exploiting the microbial gene resource of those environments demands a new approach via uncultured methods. Thanks to the development of metagenomics and bioinformatic softwares, we can exploit novel genes from environment directly. Based on Binh Chau hotspring’s DNA metagenome sequencing, ORF [denovogenes]_32768 encoding for β-glucosidase is selected for expression into pET17b vector because it shown a low similartity of amino acid sequence as compared to others in Genbank, a high alkali and Tm predicted values. To improve the expression efficiency of β-glucosidase, some factors (host strains, medium culture, IPTG concentration, aeration…) are investigated. The results showed that the recombinant E. coli C43(DE3) reached the highest dried biomass at 8.26 g/L and the maximum enzymatic activity at 0.34 U/mL in shaking condition (TB medium plus 0.25 mM IPTG with the ratio of cultured /flask volume is 20%, 42-48 hours, 30°C). This study demonstrates the capacity of mining a novel gene encoded for enzyme from DNA metagenome of Vietnam hot spring as well as produces recombinant enzyme for biomass conversion.